2019
DOI: 10.1111/jgh.14784
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tolvaptan short‐term response in patients with refractory ascites: A meta‐analysis

Abstract: Background and Aim Tolvaptan represents an oral V2‐receptor antagonist, which has been suggested as a promising add‐on diuretic treatment for refractory ascites. The present meta‐analysis aims to accumulate current evidence and identify which clinical and laboratory factors are linked to short‐term response to tolvaptan therapy. Methods Medline, Scopus, Cochrane Central Register of Controlled Trials, http://Clinicaltrials.gov, and Google Scholar databases were searched from inception. All observational studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…In addition, we indicated that serum BUN, copeptin and ZAG levels were independent predictors of the overall response to tolvaptan therapy. We further showed that serum creatinine and cystatin C levels were not predictive of patient response to tolvaptan, thus con rming the ndings reported by others 14,15 . In LC, arteriolar vasodilation causes under lling of the systemic arterial vascular space, and the decrease in the effective blood volume leads to a decrease in arterial pressure 21 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, we indicated that serum BUN, copeptin and ZAG levels were independent predictors of the overall response to tolvaptan therapy. We further showed that serum creatinine and cystatin C levels were not predictive of patient response to tolvaptan, thus con rming the ndings reported by others 14,15 . In LC, arteriolar vasodilation causes under lling of the systemic arterial vascular space, and the decrease in the effective blood volume leads to a decrease in arterial pressure 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, in this study, ZAG correlated with body weight, BMI and CRP. Bellos also reported that body weight loss and elevated CRP were the predictors for Non-responders to tolvaptan 15 . We assumed that association of serum ZAG with multiple factors including renal function, cachexia (relating to body weight and BMI) and/or in ammation (relating to CRP) led to the result.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, since hepatotoxicity represents the main concern about the wide use of tolvap- tan in cirrhotic patients [39], it is important to develop accurate screening tests that would identify tolvaptan nonresponders, in order to limit its unnecessary administration. More specifically, it has been shown that tolvaptan response may be associated with body weight, blood urea nitrogen, serum creatinine, C-reactive protein, and serum sodium levels, while no predictive value has been estimat-ed for patients' age, gender, MELD-Na score, or presence of hepatocellular carcinoma [40]. In addition, similarly to prediction of hepatorenal treatment response [41], urinary sodium has been proposed as a promising marker of tolvaptan response [35], although limited evidence is currently available to draw safe conclusions about its exact role.…”
Section: Implications For Current Clinical Practice and Future Researchmentioning
confidence: 99%